2012
DOI: 10.2139/ssrn.2402267
|View full text |Cite
|
Sign up to set email alerts
|

Production Efficiency of Family Farms and Business Farms in the Brazilian Regions

Abstract: This paper aims to analyze the technical efficiency of farms in Brazil and its regions, based on the data from the 2006 Census of Agriculture. More specifically, it seeks to compare the technical efficiency of family farms in relation to business farms, considering the regional differences in the country. To do so, one simultaneously estimated, under different assumptions, stochastic production frontiers and inefficiency effects models. Thus, it was possible to measure the technical efficiency of farms, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They considered rainfall anomalies (i.e., rainfall above or below the national average) as one of the main determinants of technical inefficiency. In Brazil, Imori et al (2012) found statistically significant impacts of temperature and precipitation on the estimated technical efficiency.…”
Section: Efficiency Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…They considered rainfall anomalies (i.e., rainfall above or below the national average) as one of the main determinants of technical inefficiency. In Brazil, Imori et al (2012) found statistically significant impacts of temperature and precipitation on the estimated technical efficiency.…”
Section: Efficiency Analysismentioning
confidence: 92%
“…Another relevant variable that influences the efficiency of farmers is farm size(Ali et al 1994, Ali & Flinn 1989, Wang et al 1996, Xu & Jeffrey 1998, Tzouvelekas et al 2001 Barrett (1996). points to an inverse relation of size and efficiency, as small farmers might use an exceptional amount of work to compensate the failures of product and credit markets that they observe.12Helfand (2003) andImori et al (2012) posit that they can lead to non-optimal choices by farmers.13Ahmed & Hossain (1990) say that rural infrastructure is the key limiting determinant of efficiency. Other studies have identified this influence by calculating the impact of the distance to markets and extension services, agricultural infrastructure, and regional differences(Rahman 2005, Tzouvelekas et al 2001) on inefficiency.…”
mentioning
confidence: 99%
“…In-depth research on the efficiency of family farms has been conducted in the theoretical community. For example, Imori et al, used stochastic production frontier and inefficiency effect models to compare and analyze the efficiency of family farms and commercial farms in Brazil and found that the efficiency of family farms was lower than that of commercial farms [8]. Madau compared the efficiencies measured by the SFA model and the DEA model, and the results demonstrated that the technical efficiency estimated by the SFA model was basically at the same level as that estimated by the DEA model; however, the scale efficiency measured by the SFA model was higher [9].…”
Section: Literature Reviewmentioning
confidence: 99%